(untitled) (Research, Society and Development, 2026)
Objective: To analyze the clinical, pathophysiological, and therapeutic aspects of adult female acne based on current scientific literature, contributing to improved diagnosis and clinical management in dermatological practice. Methodology: A narrative literature review was conducted using PubMed, SciELO, and MEDLINE databases. Studies published between 2013 and 2024 in Portuguese and English addressing clinical, pathophysiological, and therapeutic aspects of adult female acne were included. Results: The analyzed studies showed that adult female acne is characterized by persistent inflammatory lesions, preferential involvement of the lower third of the face, and a chronic course with frequent recurrence. Peripheral androgen hypersensitivity, persistent inflammation, and the role of the cutaneous microbiome were highlighted. Combined therapeutic approaches and long-term maintenance strategies demonstrated superior clinical outcomes and reduced recurrence rates. Conclusion: Adult female acne should be recognized as a distinct clinical entity, requiring individualized and long-term management based on accurate diagnosis, pathophysiological understanding, and appropriate therapeutic planning.